THE INVIGILATION OF GOVERNMENTAL SERVICES AND THE RIGHT TO PRIVACY IN THE CONTEXT OF THE SECURITY POLICY THE REPUBLIC OF POLAND - K. Khmelyazh (Гуманитарные и юридические исследования)
In the era of global technological development, the modern state is obliged to ensure security and, above all, to counter internal threats to the state, including espionage, terrorism, arms trafficking, extremism, the disclosure of classified information or even cybercrime. Ensuring security is the responsibility of the state, which must protect its citizens from threats, acting rationally and striving to reduce their sense of danger and uncertainty. This is mainly due to the security policy, which should organize the activities of the competent authorities in order to ensure the safety of society. In addition, a properly functioning political system should respond to all threats to the state that are political and domestic in nature, such as political desta-bilization, political upheaval, events that violate the constitutional, legal or economic order in the country. The study focused on attempts to understand the processes taking place in this reality, the specific consequences of which are determined by specific reasons, taking into account the context of the dependence of actual (empirical) argumentation and logical correctness. The study used a mixed research scheme, which allowed us to study the same facts as a result of combining different methods with the predominance of quantitative methods. When planning the study, it was assumed that the duration of the time series used would depend on the availability of statistical data for individual variables of the studied areas. The documentary source of the research became the received published and unpublished information from government services and authorities, including on the extent of the application of operational control and the degree to which telecommunications data were obtained.